2006
DOI: 10.1523/jneurosci.2069-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of h-Channels in Hippocampal Pyramidal Neurons by p38 Mitogen-Activated Protein Kinase

Abstract: Hyperpolarization-activated cyclic nucleotide-gated ion channels (h-channels; I h ; HCN) modulate intrinsic excitability in hippocampal and neocortical pyramidal neurons, among others. Whereas I h mediated by the HCN2 isoform is regulated by cAMP, there is little known about kinase modulation of I h , especially for the HCN1 isoform predominant in pyramidal neurons. We used a computational method to identify a novel kinase modulator of h-channels, p38 mitogen-activated protein kinase (p38 MAPK). Inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 59 publications
(62 reference statements)
7
102
0
Order By: Relevance
“…Future biochemical and functional studies are needed to address whether this decreased synaptic transmission may be due, in part, to neuronal calcium channel inhibition by channel interaction with PP2a. Alternatively, other voltage-gated ion channels, including sodium channels (Wittmack et al, 2005) and HCN (hyperpolarization-activated cyclic nucleotide)-gated channels (Poolos et al, 2002(Poolos et al, , 2006, are newly discovered potential targets for the A 1 receptor-mediated p38 MAPK activation that could play additional roles in decreasing membrane excitability and synaptic depression.…”
Section: Discussionmentioning
confidence: 99%
“…Future biochemical and functional studies are needed to address whether this decreased synaptic transmission may be due, in part, to neuronal calcium channel inhibition by channel interaction with PP2a. Alternatively, other voltage-gated ion channels, including sodium channels (Wittmack et al, 2005) and HCN (hyperpolarization-activated cyclic nucleotide)-gated channels (Poolos et al, 2002(Poolos et al, , 2006, are newly discovered potential targets for the A 1 receptor-mediated p38 MAPK activation that could play additional roles in decreasing membrane excitability and synaptic depression.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane phosphoinositides, including phosophatidylinositol-4, 5-bisphosphate (PIP 2 ) 16,40,42,44 and extracellular and intracellular chloride 45 , non-receptor tyrosine kinase c-Srcl 46,47 and p38-MAP kinase (P38MAPK) 40,48 are few of the several modulators of HCN channels.…”
Section: Regulation Of Hcn Channelsmentioning
confidence: 99%
“…Providing the large overlap between AD and VaD in clinical symptomatology, pathophysiology and neurochemical mechanisms [60][61][62][63], an effective treatment for AD may also offer benefits as a symptomatic treatment in VaD. Although most of the effects of antidepressants have been ascribed to their functions of neurogenesis activity, neurotrophin modulation and reduction of proteotoxicity [64][65][66][67], it is possible that acting on HCN channels may also contribute to or be responsible for antidepressants' efficacy on dementia since there is an interaction between the serotonergic systems and HCN channels [68][69][70] and SSRI antidepressants inhibit 5-HT reuptake that can regulate the properties and trafficking of HCN channels via a way of activating PLC-PKA and p38-MAPK signaling pathways (Figure 2) [54,[71][72][73]. It is worth mentioning that we have recently observed that fluoxetine can ameliorate cognitive impairments induced by CCH via down-regulation of HCN2 surface expression in the hippocampal CA1 area in rats (The data have not been published) and data from others also have showed that SB202190, a p38-MAPK inhibitor, can significantly reduce neuronal apoptosis in the hippocampus and rescue spatial learning and memory deficits in a rat model of vascular dementia [74].…”
Section: Reviewmentioning
confidence: 99%